Impact of Climate Change on Integrated Management of Water Resources in The lower Basin of Diyala River, Iraq - Ruaa Talib; Mohammed S. Shamkhi (Wasit Journal of Engineering Sciences)
Climate change could affect the world's water resources system, especially at the level of the basin. Climate change would impact streamflow and corresponding future water resources. The lower basin of the Diyala River is currently experiencing water shortage and contamination issues. This study aims to use Water Evaluation And Planning (WEAP) model to create an integrated modeling system for evaluating the effects of climate change on water supply and demand within the lower Diyala River basin. The WEAP model was calibrated and verified employing monthly streamflow data from the Diyala River outflow station. Following that, the calibrated model was loaded with various future scenarios ranging from 2020-2045. Future scenarios used included the reference scenario, the high population growth rate scenario, and the climate change scenario. The results indicated that the WEAP model accurately predicted the basin's water supply and demand, with RMSE, NSE, and R² values of 0.85, 0.91, and 0.867, respectively, throughout the validation period. Furthermore, Water demand and supply were found to be unmet in all projected future scenarios, showing that sustainable water management in the lower basin of the Diyala River is highly required.